THE EFFECT OF HYGIENE FACTORS AND MOTIVATING FACTORS ON ASN JOB SATISFACTION AT THE TULUNG SELAPAN DISTRICT OFFICE - Windi Lawinsi; Asmanita Asmanita (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2022)
The research purpose is to test and analyze the influences of hygiene factors and motivating factors on ASN job satisfaction in the district office at Tulung Selapan. The type of data used in this study is primary and secondary data. Primary data was obtained through observations, interviews, and surveys using an armature. Whereas secondary data is in the form of documents, references relating to research needs, and compatibility. The object of this study is ASN in the district office of Tulung Selapan, Ogan Ilir. In this study, it was made to sample as many as 22 ASN. Data collection is carried out by survey method using sequential media in the form of a questionnaire. This research uses a descriptive research method with a quantitative approach. The analyzer uses a statistical test, the t-test, and F-test. Research results obtained are Hygiene and Motivating Factors to have a significant influence on Job Satisfaction in the district office Tulung Selapan.